Spirituality in people with advanced chronic obstructive pulmonary disease – challenge for more effective interventions, support, and healthcare education: Mini-review - Kotlińska-Lemieszek, Aleksandra; Fopka-Kowalczyk, Małgorzata; Krajnik, Małgorzata (Frontiers in Medicine, 2022)
More recently there has been a growing interest in spirituality in medicine, especially in the field of palliative care, oncology, intensive care, and cardiology. However, according to literature, it seems to be a limited number of researches on how healthcare professionals should provide spiritual care (SC) for people with non-malignant lung diseases and what kind of education for them enables them to do it efficiently. This mini-review aims to provide an overview of current knowledge of an area of spirituality and SC for people with advanced chronic obstructive pulmonary disease, including spiritual well-being and religious/spiritual coping, their relations with the quality of life and symptom burden, exercise capacity and daily functioning, mental health, or medication adherence. It also analyses the use of interventions to meet patients’ spiritual needs and patients’ expectations regarding SC provided by professional careers. Based on the literature authors try to show the fields that should be improved and proposed future research directions.